Inventory of Bird Species in Kedung Kopong and Banyak Angkrem, Kec. Salaman, Kab. Magelang - H, Ikmal Maulanal; Amirisianti; Kumailiyah, Nurul; Maulany, Siti Lathifah; N, Sri Nur Haidahtun (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Kedung Kopong waterfall area which is located in Glagah Village, and the mountain area Banyak Angkrem which have an altitude of 753 meters above sea level are located in Kalirejo Village, Kec. Salaman, Kab. Magelang, Central Java is a tourist area which is an ideal bird habitat. The existence of bird habitat in tourist areas has the potential to experience disruption due to tourist visiting activities. As a result, the vegetation areas, which are the most important bird habitats, are decreasing so that it is feared that many bird species will lose their habitat. The absence of data on the birds in the area, it is necessary to conduct research to obtain information on the variety of bird species in the area along with the mount of bird. This research was conducted on March 1st 2020 - March 15th 2020, every Saturday and Sunday. The data collection time in this study was adjusted to the weather situation in Kalirejo Village, Salaman District, Magelang Regency. Observation of bird species that have diurnal activity is divided into 2 sessions. This research method is to use the exploration method (explore) directly in the field in the area of Kedung Kopong and Banyak Angkrem. Data collection was carried out by tracing the existing footpaths and hiking trails. Inventory of bird species in the tourist area of Curug Kedung Kopong and the hill of Banyak Angkrem found a variety of different species. The Tesia team found around 26 species from 17 families in the two areas, were successfully identified.